Development of the technology for manufacturing the bracket for mounting the reducer of the metropolitane cars - Biriukov , S. V.; Chukhlib, V. L. (Theory and Practice of Metallurgy, 2026)
This article discusses the developed technology for manufacturing a gearbox mounting bracket used on rolling stock in domestic metro systems. The article also analyses the design of this bracket and the malfunctions that may occur during operation. The specific nature of metro rolling stock operation, characterised by high traffic intensity, frequent acceleration and braking cycles, and significant dynamic loads, places increased demands on the reliability of each structural element of its running gear. Since a significant part of the bogie parts are manufactured using metal pressure processing methods, the issue of improving the quality of stamped forgings becomes a relevant technical task that affects the safety of passenger transport and the accident-free operation of vehicles. This article analyses other works related to improving the mechanical characteristics of products and increasing their quality, which depend on the parameters and methods of their production. The traditional forging technology discussed above usually involves a multi-stage process that includes the use of rolling grooves for preliminary distribution of metal along the axis of the blank. However, this approach increases the size of the stamping equipment and requires more passes, which leads to higher energy costs and production costs. The authors proposed abandoning the use of a rolling groove, since it is possible to manufacture this forging without changing the geometry of the blank before bending. The results of this work can be used by technologists and engineers in the machine-building industry as one of the promising ways to improve and rationalise the stamping of forgings with similar geometry, since by reducing the number of stamping passes, it is possible to reduce the cost of production and manufacture of dies without significantly affecting the stress-strain state of the resulting forging. The expediency of using computer modelling in the design of production technology is also indicated, as it allows all stages of production to be investigated without significant financial costs and ways to improve and rationalise technological operations to be identified, which will have an impact on improving the quality of manufactured products in the future.